The effectiveness of ketorolac and tramadol versus ketorolac in post-CS pain a randomized controlled trial - Mariano, Ma. Zenaida M
Objective: To compare the analgesic and safety of multimodal analgesia using the combination of intravenous (IV) ketorolac 15 mg (K15) and tramadol 50 mg (T50) to ketorolac 30 mg (K30) IV, all drugs given every 8 hours to lower the pain scores using the visual analogue scale (VAS) after low segment cesarean section(LSCS) during the study period of 12 hours. Design: Double-blind, randomized controlled trial, parallel, double-blind, two-arm. Setting: The study was done in four institutions namely Dr. Jose Fabella Hospitsl, Quirino Memorial Medical Center, Armed Forces of the Philippines Medical Center and Manila Central University Hospital. Participants: Eighty-four American Society of Anesthesiologists Physical Status I to II pregnant patients for LSCS under spinal anesthesia, who gave their informed consent, were recruited from the four participating institutions and enrolled in the study. Intervention: Patients were given either the combination of K15 IV with T50 IV every eight hours or the single agent K30 IV every eight hours. Both groups were allowed a maximum number of four rescue medications of tramadol 25 mg IV every 30 minutes as needed for a pain score of VAS 4 and above. Main Outcome Measures: The primary outcome measure was the mean pain intensity difference scores on the 2nd and 8th hour. Secondary outcomes were the mean visual VAS scores at rest and on movement at 0, 2nd and 8th hour, mean time to request the first rescue medication, mean number of rescue medication in 12 hours and occurrence of side effects (hypotension, bradycardia, respiratory depression, nausea, vomiting, pruritus, rashes. Euphoria and dizziness). Results: There was no statistical significance with the mean PID scores, mean time to request for the first rescue medication and mean total number of rescue medication for the intention-to-treat(ITT) and per protocol analysis (PPA). Repeated measures ANOVA (RMA) showed no significant interaction at rest and on movement for ITT and PPA. The difference in the mean VAS scores did not differ over time between the two groups. There was one patient who had nausea and vomiting on the 15th minute in Group KT. The symptoms disappeared spontaneously and did not require medical intervention. There were no other side effects. Conclusions: There was no sufficient evidence to reject the null hypotheses due to low power of the study. The combination of low dose K15 and T50 was effective and safe in lowering the pain intensity after uncomplicated LSCS. There was no serious adverse event reported in the patients and their babies in both groups